Genome-wide patterns of gene flow across a house mouse hybrid zone - Teeter, Katherine C.; Payseur, Bret A.; Harris, Leslie W.; Bakewell, Margaret A.; Thibodeau, Lisa M.; O’Brien, Janelle E.; Krenz, James G.; Sans-Fuentes, Maria A.; Nachman, Michael W.; Tucker, Priscilla K. (Genome Research, 2008)
Hybrid zones between closely related species or subspecies provide useful settings for studying the genetic architecture of speciation. Using markers distributed throughout the mouse genome, we use a hybrid zone between two recently diverged species of house mice (Mus musculus and Mus domesticus) as a natural mapping experiment to identify genomic regions that may be involved in reproductive isolation. Using cline analysis we document a nearly 50-fold variation in level of introgression among markers. Some markers have extremely narrow cline widths; these genomic regions may contribute to reproductive isolation. Biological processes associated with these narrow clines include physiological and immune responses to the environment as well as physiological and behavioral aspects of reproduction. Other autosomal markers exhibit asymmetrically broad clines, usually with high frequencies of M. domesticus alleles on the M. musculus side of the hybrid zone. These markers identify genome regions likely housing genes with alleles that are spreading from one species to the other. Biological processes associated with these wide clines include cell signaling, olfaction, and pheromone response. These processes play important roles in survival and reproduction, and associated genes are likely targets of selection. Patterns of linkage disequilibrium in the center of the hybrid zone suggest that isolation may be caused by multiple epistatic interactions between sets of genes. These data highlight the complex genetic architecture underlying speciation even at early stages of divergence and point to some of the biological processes that may govern this architecture.
10.1101/gr.6757907